Isolation of protoplasts from cardamom (Elettaria cardamomum Maton.) and ginger (Zingiber officinale Rose.) - Ravindran, K V Peter, S P Geetha, K Nirmal Babu, J Rema, P N (Journal of Spices and Aromatic Crops, 2000)
Protoplasts were isolated from leaf mesophyll tissue, collected from in vitro grown plantlets and cell suspension cultures of cardamom (Elettaria cardamomum) and ginger (Zingiber oJficinale). In cardamom, a protoplast yield of 3.5 x 105/ g of leaf tissue was obtained when incubated in an enzyme solution containing 0.5% macerozyme RIO, 2% cellulase Onozuka RIO and 9% mannitol for 18-20 h at 25°C in dark. The yield of protoplasts from cell suspension culture was 1.5 x 105 / g tissue, when incubated in I % macerozyme RIO and 2% cellulase Onozuka RIO for 24 h at 25°C with gentle shaking at 53 rpm in dark. The viability of leaf mesophyll protoplast was 75% and that of cell suspension was 40% on Evan’s blue staining. In ginger, a protoplast yield of 2.5 x lOS / g of leaf tissue was obtained on digestion in an enzyme solution containing 0.5% macerozyme RIO, 3% hemicellulase and 5% cellulase Onozuka RIO, when incubated for 10 h at 15°C followed by 6 h at 30°C. The protoplast viability was 55%. Protoplast yield from cell suspension culture was 1 x lOS /g of callus when digested with an enzyme solution of I % macerozyme RIO, 3% hemicellulase and 6% cellulase Onozuka RIO and incubated for 10h at 15°C and later at 30°C for 8 h. Seventy two per cent of the protoplasts were viable. The protoplasts from both the species could be cultured and made to develop up to microcalli stage.